Strategies for hydration and energy provision during soccer-specific exercise - Clarke, N. D.; Drust, B.; MacLaren, D. P. M.; Reilly, T. (International Journal of Sport Nutrition and Exercise Metabolism, 2005)
The aim of the present study was to investigate the effect of manipulating the provision of sports drink during soccer-specific exercise on metabolism and performance. Soccer players (N = 12) performed a soccer-specific protocol on three occasions. On two, 7 mL/kg carbohydrate-electrolyte (CHOv) or placebo (PLA) solutions were ingested at 0 and 45 min. On a third, the same total volume of carbohydrate-electrolyte was consumed (CHOf) in smaller volumes at 0, 15, 30, 45, 60, and 75 min. Plasma glucose, glycerol, non-esterified free fatty acids (NEFA), cortisol, and CHO oxidation were not significantly different between CHOv and CHOf (P > 0.05). Sprint power was not significantly affected (P > 0.05) by the experimental trials. This study demonstrates when the total volume of carbohydrate consumed is equal, manipulating the timing and volume of ingestion elicits similar metabolic responses without affecting exercise performance.